"Coming to a Strange Land": The West African Migrant Women's Establishment of Home and Family in a New Culture Within Australia. (September 2016) - Babatunde-Sowole, Olutoyin O; Jackson, Debra; Davidson, Patricia M; Power, Tamara
Purpose: Migrating and establishing a new life in another culture can have diverse health effects especially for women. This article explores the struggles and social adjustment issues that might constitute negatively to the health of West African migrant women living in Australia.Design: Qualitative storytelling. Audiotaped voluntary stories from 20 West African migrant women living in Sydney, Australia were transcribed and analyzed.Findings: Three themes are presented for discussion: (1) But it is different here : life in a new country; (2) I have to do it all by myself : communal versus individual living; and (3) They don't listen to parents : perceived threats to the family unit.Conclusion/Implication for Practice: The demand for and the importance of nurses and midwives in supporting migrant families is demonstrated by findings suggesting that social adjustment into the Australian culture has a significant impact on both the nuclear and extended family unit of women.